2018
DOI: 10.5007/2177-5230.2018v33n68p184
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial e temporal da precipitação de Santa Catarina

Abstract: O objetivo deste trabalho é caracterizar a variabilidade espacial e temporal da precipitação de Santa Catarina, verificando tendências e ciclos nas suas séries históricas. Foram analisadas 127 séries pluviométricas, distribuindo-as espacialmente, dividindo-as em seis regiões homogêneas. Selecionou-se estações pluviométricas representativas de cada região, que foram submetidas aos testes de Mann Kendall e Sen (análise de tendências) e à Análise de Ondaletas para observação do comportamento temporal da precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Average rainfall values (mm/year), intra-and interannual averages (A) of gauges in the Fortaleza River catchment, *Missing values, lled by Iporã do Oeste meteorological station -Santa Catarina.The t test demonstrated that there is no signi cant difference between the monthly observations. The absence of difference is consistent with the study byBaptista and Severo (2018), which also found a homogeneous distribution of rainfall in the region over the range of years 1984 to 2014. In relation to annual precipitation, the highest annual rainfall was measured in 2015, with 2,562.2 mm/year, and the lowest in 2020, with 1,474.1 mm/year.Monthly precipitation showed a decreasing trend according to the Mann-Kendall test (z = −2.04, p-value = 0.041).…”
supporting
confidence: 92%
“…Average rainfall values (mm/year), intra-and interannual averages (A) of gauges in the Fortaleza River catchment, *Missing values, lled by Iporã do Oeste meteorological station -Santa Catarina.The t test demonstrated that there is no signi cant difference between the monthly observations. The absence of difference is consistent with the study byBaptista and Severo (2018), which also found a homogeneous distribution of rainfall in the region over the range of years 1984 to 2014. In relation to annual precipitation, the highest annual rainfall was measured in 2015, with 2,562.2 mm/year, and the lowest in 2020, with 1,474.1 mm/year.Monthly precipitation showed a decreasing trend according to the Mann-Kendall test (z = −2.04, p-value = 0.041).…”
supporting
confidence: 92%
“…The high altitudes of Dionísio Cerqueira and Xanxerê and the proximity to the ocean in the municipality of Laguna may be the main reasons for the increased precipitation in these regions. According to the study by Baptista, Severo (2018), between the western region and the Santa Catarina Plateau where Dionísio Cerqueira and Xanxerê are located, the annual total precipitation compared to the coast is higher, between 1,900 and 2,000 mm (West) and between 1,600 and 1,700 mm (Santa Catarina Plateau).…”
Section: Resultsmentioning
confidence: 99%
“…Similar heat sum values were found in the literature for the climatic conditions of Santa Maria, in the State of Rio Grande do Sul, at different planting dates and for different cultivars, ranging from 849.5 to 1112.7°C day for the vegetative phase and from 215.7 to 312.5ºC day for the reproductive phase (STRECK et al, 2012). Rainfall is regularly distributed in the different regions of Santa Catarina throughout the year but was possible identify periods with high and low rainfall (BAPTISTA & SEVERO, 2018). Phenomena such as El Niño Southern Oscillation (ENSO) also influence the climatic conditions in several regions and can modify the rainfall regime (POWER & DELAGE, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Rainfall distribution varies between locations over the months (BAPTISTA & SEVERO, 2018). A study to characterize the annual rainfall rates in the State did not identify locations with defined dry seasons, considering a 75% probability of rainfall occurrence (COAN et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation